Functional metagenomics unveils a multifunctional glycosyl hydrolase from the family 43 catalysing the breakdown of plant polymers in the calf rumen. - Manuel Ferrer (Public Library of Science (PLoS), 2012)
Microbial communities from cow rumen are known for their ability to degrade diverse plant polymers at high rates. In this work, we identified 15 hydrolases through an activity-centred metagenome analysis of a fibre-adherent microbial community from dairy cow rumen. Among them, 7 glycosyl hydrolases (GHs) and 1 feruloyl esterase were successfully cloned, expressed, purified and characterised. The most striking result was a protein of GH family 43 (GHF43), hereinafter designated as R_09-02, which had characteristics very distinct from the other proteins in this family with mono-functional β-xylosidase, α-xylanase, α-L-arabinase and α-L-arabinofuranosidase activities. R_09-02 is the first multifunctional enzyme to exhibit β-1,4 xylosidase, α-1,5 arabinofur(pyr)anosidase, β-1,4 lactase, α-1,6 raffinase, α-1,6 stachyase, β-galactosidase and α-1,4 glucosidase activities. The R_09-02 protein appears to originate from the chromosome of a member of Clostridia, a class of phylum Firmicutes, members of which are highly abundant in ruminal environment. The evolution of R_09-02 is suggested to be driven from the xylose- and arabinose-specific activities, typical for GHF43 members, toward a broader specificity to the glucose- and galactose-containing components of lignocellulose. The apparent capability of enzymes from the GHF43 family to utilise xylose-, arabinose-, glucose- and galactose-containing oligosaccharides has thus far been neglected by, or could not be predicted from, genome and metagenome sequencing data analyses. Taking into account the abundance of GHF43-encoding gene sequences in the rumen (up to 7% of all GH-genes) and the multifunctional phenotype herein described, our findings suggest that the ecological role of this GH family in the digestion of ligno-cellulosic matter should be significantly reconsidered.